1999
DOI: 10.1053/euhj.1999.1632
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of symptomatic paroxysmal atrial fibrillation. Data from almost 10000 episodes

Abstract: The onset of paroxysmal atrial fibrillation does not occur randomly. The large patient population in the present study suggests that the circadian rhythm of paroxysmal atrial fibrillation is similar to that described for other cardiovascular diseases, with clustering of events in the morning and (to a lesser degree) late in the evening. Weekly and yearly circadian patterns are also prominent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 19 publications
3
50
0
4
Order By: Relevance
“…This reduction was most apparent in the early morning, when the incidence of AF is highest. 154 Histologically, LL-VNS resulted in a significant reduction of ganglion cells in the LSG that were stained positive for tyrosine hydroxylase, an enzyme critical in the biosynthesis of adrenalines ( Figure 8A). A subsequent study by the same group showed that in the LSG, LL-VNS also resulted in the upregulation of small-conductance calcium-activated potassium channel type 2 and increased its expression in the cell membrane ( Figure 8B and 8C).…”
Section: Neural Stimulationmentioning
confidence: 99%
“…This reduction was most apparent in the early morning, when the incidence of AF is highest. 154 Histologically, LL-VNS resulted in a significant reduction of ganglion cells in the LSG that were stained positive for tyrosine hydroxylase, an enzyme critical in the biosynthesis of adrenalines ( Figure 8A). A subsequent study by the same group showed that in the LSG, LL-VNS also resulted in the upregulation of small-conductance calcium-activated potassium channel type 2 and increased its expression in the cell membrane ( Figure 8B and 8C).…”
Section: Neural Stimulationmentioning
confidence: 99%
“…The study conducted on a large population (32,992) in Denmark revealed a noticeable increase in the incidence of AF episodes in winter, a decrease in summer as well as an association between these episodes and outdoor temperature (Frost et al 2002). Similarly, two studies on the seasonality of paroxysmal AF, in Israel (Viskin et al 1999) and Finland (Kupari and Koskinen 1990), found the peak incidence during winter despite the fact that the average temperatures in both countries vary considerably. On the other hand, according to findings from one Japanese study, the incidence of AF paroxysms was the highest in autumn and the lowest in summer (Watanabe et al 2007).…”
mentioning
confidence: 92%
“…Viskin et al showed circadian variation in the incidence of symptomatic AF in humans, an observation that indicated the importance of the ANS in atrial arrhythmogenesis. 13 In the study by Tatsuishi et al 2 in this issue of the Journal, in addition to BS, another significant, and potentially independent risk factor of post-CABG AF was postoperative drainage volume. However, the focus of that study was the relationship between BS and AF, and drainage volume was not assessed further.…”
Section: Article P 112mentioning
confidence: 94%